The Impact of Audio Play on Awareness and Practice of Menstrual Hygiene between Visually Challenged Adolescent Girls - Sherin Nithya.S, Geetha .C (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Menstrual health is a comprehensive condition of physical, mental, and social well-being, not only the absence of sickness or disability related to the menstrual cycle.(WHO2018). OBJECTIVES: To determine the impact of AI audio play on awareness and practice on menstrual hygiene among visually challenged Adolescent girls. METHOD: The researchers used a quantitative method to analyse 45 visually impaired girls, selecting them using a purposive sampling technique and utilizing a pre-experimental one-group pre-test post-test design. Pre existing knowledge was assessed by using semi structured interview questionnaires and practice was assessed by self reporting practice check list. After the pre test, menstrual practices were thought by AI audio play to the Visually Challenged Girls on hygiene. After 3 weeks post test was done through using the same tool. RESULT: There was an insufficiency of awareness and practices on menstruation before the interventions of audio play short term sessions prepared through Artificial Intelligence. Also, there were an improvement and highly statistically significant differences in the total scores of awareness and practices of visually challenged girls regarding menstruation after the AI audio play on appropriate menstruation practices. (P<0.001). CONCLUSION: Girls who are visually challenged benefited from listening to an Audio play prepared through AI on menstrual hygiene, which increased their awareness and adherence to the best practices.